2017
DOI: 10.14198/jhse.2017.122.11
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and emotional influence on heart rate recovery after submaximal exercise

Abstract: The purpose of this study was to assess the role of cardiovascular fitness and emotional state in heart rate recovery after submaximal exercise. Fifty recreationally active subjects (male n=19, females n= 31) completed the study. Height, weight, body composition, and waist circumference were measured, with current emotional state assessed through completion of the Profile of Mood States questionnaire, followed by the Queen's College Step Test to estimate maximal oxygen consumption (VO2max). Heart rate recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…This model explained that after administering a stress task, the cognition can lead to experience some negative emotions (e.g., sadness or anxiety), and these negative emotions can increase sympathetic arousal prolonging negative emotions (and vice‐versa). Differently, other studies reported that the cardiovascular recovery was relatively faster for unemotional tasks compared to emotional tasks (e.g., mental arithmetic with harassment; Bunn, Manor, Wells, Catanzarito, Kincer, & Eschbach, 2017; Linden, Earle, Gerin, & Christenfeld, 1997).…”
Section: Introductionmentioning
confidence: 78%
“…This model explained that after administering a stress task, the cognition can lead to experience some negative emotions (e.g., sadness or anxiety), and these negative emotions can increase sympathetic arousal prolonging negative emotions (and vice‐versa). Differently, other studies reported that the cardiovascular recovery was relatively faster for unemotional tasks compared to emotional tasks (e.g., mental arithmetic with harassment; Bunn, Manor, Wells, Catanzarito, Kincer, & Eschbach, 2017; Linden, Earle, Gerin, & Christenfeld, 1997).…”
Section: Introductionmentioning
confidence: 78%
“…This result could be explained by hyperactivation of the PNS via central, cardiac, and/or peripheral mechanisms as suggested by some authors [ 19 , 20 ]. This decrease in resting HR in athletes could also be due to training, which could induce an increase in plasma volume, allowing for a greater stretch of the heart and an increase in stroke volume, as well as a greater sensitivity of the PNS, thus improving the physical condition of the subject undergoing this training [ 18 , 21 ]. Indeed, optimal physical conditioning, coupled with adequate recovery, creates a healthy “imbalance” between the activities of the sympathetic and parasympathetic nervous systems in favour of greater vagal dominance.…”
Section: Resultsmentioning
confidence: 99%